Literacy Skills of Students in a Remote Area - Ramayanti, Rory; Iranda, Agung; Yusufhin, Fridinanti (Universitas Wijaya Kusuma Surabaya, 2024)
Purpose Research. The research objective was to identify the literacy skills of Merangin 53 Remote Junior High School students. Research Method. This study used a qualitative method with an ethnographic approach. The data were collected through interviews, observation, and documentation. Analysis Data. The Spradley model was used in the analysis. The analysis steps consisted of determining participants, interviewing, making an ethnographic record, asking descriptive questions, analyzing the interviews, making a domain analysis, asking structural questions, making a taxonomic analysis, asking contrast questions, discovering cultural themes, and writing an ethnography Results. Literacy topics of Merangin 53 Junior High School students encompassed access to information, lack of literacy skills, literacy learning methods that rely on the teacher, guidance and mentoring, and literacy for effective school activity. Conclusions. Some topics collected from literacy skills included the influence of culture and the situation in the remote school. Some influences on literacy skills encompassed difficult access to roads, internet connections, transportation, and students' socioeconomic conditions. Keywords: Information literacy, remote school, Merangin